Pengembangan Potensi Wisata Desa Surau Kecamatan Taba Penanjung Kabupaten Bengkulu Tengah - Oktaviani, Oktaviani; Isnaini, Desi; Polindi, Miko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This service was carried out in Surau Village, Taba Penanjung District, Central Bengkulu Regency, this service aims to support the development of tourism potential in Surau Village. In this service activity, researchers used the ABCD (Asset-Based Community Development) method. The focus of this activity is to create social media accounts as promotional material for village tourism. The ABCD method in this service activity is carried out in stages: a. Discovery (Asset Identification), b. Dream (building relationships and collaboration), c. Design (designing targets), d. Define (determine), e. Destiny (do). The results of the activity show an increase in community capacity in tourism management, Pokdarwis, as well as the creation of a digital-based marketing strategy to increase the tourist attraction of the village. With this development, it is hoped that Surau Village can become one of the leading tourist destinations in Central Bengkulu Regency which will ultimately support the sustainable economic growth of the local community.